PENGARUH HASIL PENGAWASAN INTERNAL DAN PENYELESAIAN TINDAK LANJUT KERUGIAN TERHADAP KINERJA KEUANGAN (Studi Pada Satuan Kerja Perangkat Daerah (SKPD) Di Kabupaten Poso) - Hasrul, Hasrul (Katalogis, 2016)
This research is aimed to determine and analyze: 1) the result of internal control and completion of follow-up losses on financial performance of The Local Governmental Work Units in Poso Regency; 2) the significant effect of internal control and completion of follow-up losses on financial performance of The Local Governmental Work Units in Poso Regency; 3) the significant effect of internal control on financial performance of The Local Governmental Work Units in Poso Regency; 4) the significant effect of follow-up losses completion on financial performance of The Local Governmental Work Units in Poso Regency. Statistical test by using multiple linear regressions with SPSS program 17.0 shows that: a) the result of internal control and completion of follow-up losses have significant effect on financial performance of The Local Governmental Work Units in Poso Regency; b) internal control has significant effect on financial performance of The Local Governmental Work Units in Poso Regency; c) follow-up losses completion has negative significant on financial performance of The Local Governmental Work Units in Poso Regency.